Altered Synaptic and Extrasynaptic NMDA Receptor Properties in Substantia Nigra Dopaminergic Neurons From Mice Lacking the GluN2D Subunit - Morris, Paul G.; Mishina, Masayoshi; Jones, Susan (Frontiers in Cellular Neuroscience, 2018)
N-methyl-D-aspartate receptors (NMDARs) are ubiquitously expressed in the mammalian brain and are essential for neuronal development, survival and plasticity. GluN2 subunit composition has a profound effect on the properties of NMDARs. In substantia nigra dopaminergic (SNc-DA) neurons, pharmacological experiments suggest that the relatively rare GluN2D subunits form functional synaptic and extrasynaptic NMDARs. Given the importance of establishing this point, mice lacking the GluN2D subunit (Grin2D-null) were used in this study to further explore the contribution of the GluN2D subunit to NMDAR responses. Significantly less DQP-1105-sensitive NMDAR-EPSC and significantly more ifenprodil-sensitive NMDAR-EPSC was observed in SNc-DA neurons from Grin2D-null mice, indicating that in these animals a small population of synaptic GluN2D subunits is replaced with GluN2B. Significantly larger currents were seen in response to higher concentrations (1-10 mM) of NMDA in SNc-DA neurons from Grin2D-null mice, as well as significantly more desensitization; these data are consistent with the presence of GluN2D-containing whole-cell NMDARs in SNc-DA neurons, with low conductance and little desensitization. Brief applications of NMDA evoked responses that were significantly less sensitive to DQP-1105 in slices from Grin2D-null mice. Tonic NMDAR activity in response to ambient extracellular glutamate, determined by the sensitivity of tonic current to D-AP5 (50 microM), was significantly less in SNc-DA neurons from Grin2D-null mice. In the presence of the glutamate transporter blocker TBOA (30 microM), the D-AP5-sensitive current was also significantly less in Grin2D-null mice. Taken together, these data support the evidence for GluN2D subunit expression in functional NMDARs at both synaptic and extrasynaptic locations in SNc-DA neurons